Leadership decapitation : strategic targeting of terrorist organizations - Jordan, Jenna (Jennifer Elaine) (Stanford, California : Stanford University Press, 2019)
One of the central pillars of US counterterrorism policy is that capturing or killing a terrorist group's leader is effective. Yet this pillar rests more on a foundation of faith than facts. In Leadership Decapitation, Jenna Jordan examines over a thousand instances of leadership targeting-involving groups such as Hamas, al-Quaeda, Shining Path, and ISIS-to identify the successes, failures, and unintended consequences of this strategy. As Jordan demonstrates, group infrastructure, ideology, and popular support all play a role in determining how and why leadership decapitation succeeds or fails. Taking heed of these conditions is essential to an effective countererrorism policy going forward. - from book cover
A theory of organizational resilience -- Hypotheses on leadership decapitation -- Is leadership targeting effective? -- Hamas : bureaucracy, social services, and local support -- The Shining Path : the organization and support of a left-wing group -- Al-Qaeda : religious ideology and organizational resilience
Includes bibliographical references and index
Keywords: Terrorism -- Prevention